2022
DOI: 10.1037/hea0001183
|View full text |Cite
|
Sign up to set email alerts
|

Health coaching and genetic risk testing in primary care: Randomized controlled trial.

Abstract: Objective: Accessible interventions are needed to prevent coronary heart disease (CHD) and Type 2 diabetes (T2D). This prospective, randomized, controlled trial evaluated remote health coaching (HC),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The baseline includes data for 200 patients (47.7 ± 11.56 years old) at primary care clinics with at least 1 risk factor for either coronary heart disease or type 2 diabetes. Further details on this previous trial including the inclusion and exclusion criteria can be found elsewhere (blinded for review) 27 . We received institutional review board approval at the university medical center of the coordinating site and participating clinical sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline includes data for 200 patients (47.7 ± 11.56 years old) at primary care clinics with at least 1 risk factor for either coronary heart disease or type 2 diabetes. Further details on this previous trial including the inclusion and exclusion criteria can be found elsewhere (blinded for review) 27 . We received institutional review board approval at the university medical center of the coordinating site and participating clinical sites.…”
Section: Methodsmentioning
confidence: 99%
“…Further details on this previous trial including the inclusion and exclusion criteria can be found elsewhere (blinded for review). 27 We received institutional review board approval at the university medical center of the coordinating site and participating clinical sites.…”
Section: Study Design and Samplementioning
confidence: 99%
“…Additionally, digital health interventions (including mHealth) and centralized telephonic interventions have the potential to reach patients where they are and when they are available in resource-sparing manner. An example of the latter is the remote health coaching intervention, which had positive effects on physical activity and mental health outcomes, evaluated in the randomized controlled trial (RCT) by Wolever and colleagues (2022). We also endorse a pragmatic trial approach (Patsopoulos, 2011) (testing interventions under real-world conditions for the patients, providers, health care systems, and so on).…”
Section: We Need To Refocus Our Science On the Clinical Research And ...mentioning
confidence: 99%
“…Several studies demonstrate the utility of CVBM within diverse areas of clinical practice, including preventative cardiology, heart failure, and cardiac rehabilitation. Wolever et al (2022) present a randomized controlled trial that investigates the interactive effects of genetic risk testing and health coaching on diet, exercise behaviors, and several secondary psychological outcomes in at-risk Air Force personnel. Vela and Feingold (2022) discuss the value and challenges of implementing CVBM within a heart transplant clinic in collaboration with key leaders and stakeholders.…”
mentioning
confidence: 99%